Age Management - a Coping Strategy for Employers. The Case of the Automotive Industry - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2006)
Globalisation and the ageing of the work force represent a dual challenge for enterprises. The first exerts pressure on production costs in order to stay competitive, the second raises production costs as the productivity of workers tends to decline after a certain age, particularly for unskilles and semiskilled workers involved in heavy physical work and where seniority-pay regimes apply. This paper looks at coping strategies of an enterprise in the automotive industry in Austria. It shows to what extent innovative and flexible organisation of work may ensure the survival of the production site in a highly developed economy, and what role public institutions play, in particular wage policy, retirement regulations and labour market policies, to keep older workers in employment. Austrian car manufacturing is a particularly interesting case as the option of outsourcing challenges the viability of Austrian production sites.
Keywords: 330; Age Management; ageing of the work force; automotive industry; Kfz-Industrie; Ältere Arbeitskräfte; Personalmanagement; Vergütungssystem; Altersgrenze; Arbeitsmarktpolitik; Österreich